Knowledge, Attitude and Socio-cultural Beliefs of Adolescent Girls towards Menstruation - Kapoor, Anju; Khari, Smriti (Journal of Nepal Paediatric Society, 2016)
Introduction: Knowledge regarding physiology of menstruation and hygienic practices are poor in adolescent girls. Deep rooted social beliefs make their attitude more negative. Material and Methods: In a hospital based cross sectional study, one hundred adolescent girls who have attained menarche were interviewed with a pre-validated semi-structured questionnaire to assess their knowledge, experiences, effect of mother’s education on menstrual hygienic practices and factors affecting their positive and negative attitude. Results: Mean age of menarche was 13.28 (SD ± 1.42) years. Mothers were the first informant to 56% girls. Only 11% girls knew that menstruation is a normal biological phenomenon and 28% girls were mentally prepared before menarche. Readymade pads were being used by 46% girls. Most girls were forced to follow various restrictions during menstruation. Maternal education was significantly associated with use of readymade pads (p-value 0.031). Significant positive correlation was seen between premenarchal preparedness to pleasantness (r = 0.3215; p = 0.001) while negative correlation was found between preparedness to secrecy (r = -0.1549; p = 0.124), annoyance (r = -0.1421; p = 0.158) and worrying thoughts (r = - 0.2074; p = 0.038). Negative correlation was also seen between years of experience with menses to secrecy and worrying thought (r = -0.0162; p = 0.872 and r = -0.1033; p = 0.864 respectively). Conclusion: There is significant lack of knowledge, poor hygienic practices and negative attitude among adolescent girls that needs to be addressed by educating them and their mothers. J Nepal Paediatr Soc 2016;36(1):42-49